SINTESIS Mg-Al-EDTA HYDROTALCITE DAN APLIKASINYA SEBAGAI ADSORBEN ION Cu2+ - , TITIN ARYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis of Mg-Al-EDTA hydrotalcite and its application as adsorbent for Cu2+ ion has been performed. This research was aimed to study the ability of Mg-Al-EDTA hydrotalcite as adsorbent of Cu2+ ion. Mg-Al-EDTA hydrotalcite was synthesised by ion exchange of NO3- in Mg-Al-NO3 with EDTA. Mg-Al-NO3 hydrotalcite was synthesised by coprecipitation method and hydrotermal treatment at 100Â°C for 15 h. Adsorption has been studied at optimum conditions by batch method. Desorption has been studied by using HNO3 0.01 M solution. Mg-Al-EDTA hydrotalcite has basal spacing (d003) 14.60 Ã. The FT-IR spectra suggested that C=O group was observed at 1605 cm-1. The optimum condition for adsorption of Cu2+ ion was obtained at pH 5, contact time 75 minutes and adsorption capacity 3.47 mg/g. Cu2+ ion was adsorbed by Mg-Al-EDTA hydrotalcite according to first order of reaction with reaction rate 9 x 10-3 min-1. Adsorption of Cu2+ ion by Mg-Al-EDTA hydrotalcite was caused by the complex formation between Cu2+ and EDTA.